Evaluation of the in vitro expression of ATP binding-cassette (ABC) proteins in an Ixodes ricinus cell line exposed to ivermectin. Issue 1 (December 2016) - Mangia, Carlo; Vismarra, Alice; Kramer, Laura; Bell-Sakyi, Lesley; Porretta, Daniele; Otranto, Domenico; Epis, Sara; Grandi, Giulio
Abstract Background Ticks are among the most important vectors of pathogens causing human and animal disease. Acaricides are used to control tick infestation, although there are increasing reports of resistance. Recently, over-expression of ATP-binding cassette (ABC) transporter proteins (P-glycoproteins, PgP) has been implicated in resistance to the acaricide ivermectin in the ticksRhipicephalus (Boophilus )microplus andRhipicephalus sanguineus sensu lato. Ixodid tick cell lines have been used to investigate drug resistance mechanisms. The aim of the present study was to evaluate expression of several PgPs in theIxodes ricinus -derived cell line IRE/CTVM19 and to determine modulation of expression following treatment with ivermectin. Findings IRE/CTVM19 cells were treated with different concentrations of ivermectin (0, 11, 22 or 33 μM) and incubated for 10 days. Evaluation of viability and relative expression of ABCB1, ABCB6, ABCB8 and ABCB10 genes were carried out at day 10 post treatment. Cell viability ranged between 84 % and 92 % with no significant differences between untreated and treated cells. qRT-PCR showed that ABC pump expression was not significantly modulated by ivermectin treatment. Expression of the ABCB8 PgP subfamily revealed a biphasic trend, based on the ivermectin concentration. ABCB6 and ABCB10 gene expression was not modulated by ivermectin treatment and ABCB1 expression was not detected. Conclusions This is the first report of PgP expression in anI. ricinus -derived tick cell line. Development of an in vitro model for the study of acaricide resistance mechanisms would greatly facilitate screening for drug resistance in ticks.